Analysis Competitiveness of Sugarcane Farming in Central Java and East Java - Wahyu Adhi Saputro; Masyhuri Masyhuri; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
This study aims to determine the competitiveness of sugarcane farming in Central Java and East Java based on comparative advantage (DRCR) and competitive advantage (PCR). The method used was the Policy Analysis Matrix (PAM). The result in Central Java explained that the sugarcane farming do not have comparative advantage but have competitive advantage. It is indicated by the value of Domestic Resource Cost Ratio DRCR>1 which is 1.23 and the value of Private Cost Ratio PCR<1 which is 0.71. Meanwhile The result in East Java explained that the sugarcane farming do not have comparative advantage but have competitive advantage. It is indicated by the value of DRCR>1 which is 1.05 and the value of PCR<1 which is 0.56. Partial test was conducted to find out how many respondents in each region in Central Java and East Java that have competitiveness sugarcane farming. Based on the partial test of each respondent in Central Java, about 51.67%, 45.00% and 3.33% of respondents are categorized as very competitive, medium competitiveness and very low competitive respectively. Meanwhile, in East Java Province, there are 25.00% of respondents with very high competitiveness, 65.00% medium competitiveness and 10.00% very low competitive.